Najpogostejša socialna problematika oseb po amputaciji spodnjih udov v Univerzitetnem rehabilitacijskem inštitutu Republike Slovenije – Soča - Stevanovič, Jolanda (Socialno delo, 2021)
The paper is based on a research study about social work with people after lower limb amputation at the University Rehabilitation Institute of the Republic of Slovenia – Soča, Department for rehabilita- tion of patients after amputation, where a social worker is a member of a multidisciplinary medicine rehabilitation team. It is the first social work study in Slovenia addressing the most frequent social problems of people after lower limb amputation. The results indicate that the majority of individuals after lower limb amputation and their relatives are poorly informed about the possibilities for help at home and the rights arising from disability, as well as with the possibilities and procedures of obtaining the rights pertaining to social, health and disability insurance. Individuals were facing difficulties in various areas, such as care and support at home, social inclusion into the community, car driving, socioeconomic status and administrative procedures.
Keywords: biopsihosocialni pristop; biopsychosocial approach; disability rights; multidisciplinarni tim; multidisciplinary team; pravice invalidov; rehabilitacija; rehabilitation; social work; socialno delo; team work; timsko delo